2016
DOI: 10.1007/s10040-016-1489-5
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flow dynamics in the complex aquifer system of Gidabo River Basin (Ethiopian Rift): a multi-proxy approach

Abstract: Hydrochemical and isotope data in conjunction with hydraulic head and spring discharge observations were used to characterize the regional groundwater flow dynamics and the role of the tectonic setting in the Gidabo River Basin, Ethiopian Rift. Both groundwater levels and hydrochemical and isotopic data indicate groundwater flow from the major recharge area in the highland and escarpment into deep rift floor aquifers, suggesting a deep regional flow system can be distinguished from the shallow local aquifers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…However, it also demonstrates the vulnerability of the shallow aquifers to surface-groundwater interactions, which results in both geochemical contamination and potential microbial contamination from surface runoff in areas with limited sanitation. Furthermore, isotope analysis of shallow aquifers in Ethiopia support earlier studies by [16] in the Gidabo basin of Ethiopia, which note the complex nature of the aquifer systems and distinct difference between the shallow and deep groundwater flows. They used δ 18 O and δ 2 H values to estimate the age of the groundwater and they concluded that there is a direct relationship between the deep groundwater flows and rainfall patterns.…”
Section: Discussionsupporting
confidence: 80%
“…However, it also demonstrates the vulnerability of the shallow aquifers to surface-groundwater interactions, which results in both geochemical contamination and potential microbial contamination from surface runoff in areas with limited sanitation. Furthermore, isotope analysis of shallow aquifers in Ethiopia support earlier studies by [16] in the Gidabo basin of Ethiopia, which note the complex nature of the aquifer systems and distinct difference between the shallow and deep groundwater flows. They used δ 18 O and δ 2 H values to estimate the age of the groundwater and they concluded that there is a direct relationship between the deep groundwater flows and rainfall patterns.…”
Section: Discussionsupporting
confidence: 80%
“…The southern Rift Valley narrows up to 60 km, shifts to a N-S trend, and reaches an elevation of 2,000 m, decreasing southward to 1,000 m (Abbate et al, 2015). The typical rift morphology is well developed and the three major physiographic regions, rift floor, escarpment and highland, are clearly visible (Mechal et al, 2017). The major tectonic scarp connects the rift floor with the uplifted plateau; the plateau rises to elevations of 3,200 m a.s.l., whereas the rift floor descends to 1,175 m a.s.l at Lake Abaya (Mechal et al, 2017).…”
Section: Study Area Descriptionmentioning
confidence: 95%
“…The area is situated roughly between 4.5 0 -12 0 N latitude and 36 0 -44 0 E longitude with an estimated total area of 243,640 square kilometers (ARBWA, 2013), which is nearly 21.4% of the total land area of the country (Fig 1). MoARD, 2005 The physiographic features of the GRVB are mainly the results of faulting and volcanism associated with rifting processes (Mechal et al, 2017). From a morphological and geological point of view, the region has been subdivided into three main segments: the northern, central, and southern (Wolde Gabriel et al, 1990;Abbate et al, 2015).…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…e quality analyses including physical parameters of color, odor, taste, turbidity, and temperature, physical-chemistry parameters such as electrical conductivity (EC), total dissolved solids (TDS), and hydrogen ion activity (pH), and chemical parameters. In general, the physics and physical-chemistry quality of groundwater can be categorized as clean water (Kusumayudha et al, 2013). Referring to the hydrochemical study by Newman et al (2016) and Katsanou et al (2017), the chemical compounds selected to be tested were: Na + , Ca 2+ , Mg 2+ , Cl -, SO 4 2-, NO 3 -, NO 2 -, HCO 3 -, Fe, and Mn (Table 1).…”
Section: Groundwater Qualitymentioning
confidence: 99%